WHAT ARE THE TYPE OF LEARNING MEDIA INNOVATION NEEDED TO SUPPORT DISTANCE LEARNING? - Hendriyanto, Agus; Kusmayadi, Tri Atmojo; Fitriana, Laila (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This exploratory qualitative article with an inductive approach aims to analyze the needs of students of the mathematics education study program at one of the leading universities in Surakarta City regarding learning media that can facilitate the implementation of distance learning during the Coronavirus pandemic. Data were obtained through distributing questionnaires using Google Form to 63 students who had taken the analytic geometry course at the beginning of the Coronavirus pandemic, interviews with 2 lecturers, and 3 students selected through snowball sampling technique. The results of the analysis showed that students need interactive audio-visual teaching materials that can be accessed easily without any internet network constraints. It is evidenced by the results of the survey which show that 70% of students need audio-video-based learning media. The results of this study become the basis for developing learning media that supports the implementation of distance learning